STRATEGI PROGRAM RADIO SIARAN ESOA DALAM UPAYA MEMPERTAHANKAN PENDENGAR DI ELSHADDAI FM - Maya Sekar Wangi, Jessyca Sarah Ferginia, Buddy Riyanto & (Transformasi, 2016)
This research is a qualitative descriptive study that describes the strategy of Programmer,Producer, Broadcaster at ESOA program to keep listeners on Elshaddai FM. Using interactivedata analysis techniques of Miles and Huberman. These results indicate that efforts intend forlisteners to continue listening stable ESOA program. Efforts made is adapt the program to theneeds of listeners in terms of concept, content, placement of airtime equal to the criteria ofSusan Tyler Eastman and Douglas A. Ferguson. Besides the use of the rundown, programappeal, and the delivery style broadcasters can attract listeners to continue listening ESOAprogram, so ESOA can still take place until today.Key words : strategy, ESOA program, retain listeners.